Characterization of Natural Resources in the Narmada Canal Project Area of Rajasthan for their Management under Canal Command Irrigation - Kumar, Mahesh; Priyabrata Santra; P. C. Moharana; Nav Raten Panwar; R K Goyal; C B Pandey (Annals of Arid Zone, 2024)
A systematic investigation was undertaken to assess the state of natural resources i.e. soils, landform, and water in response to continuous canal irrigation in the Narmada Canal Project area in two arid districts of arid Rajasthan. Soils in the NCP area in Rajasthan were found very deep, slightly to strongly alkaline in reaction (pH 7.62 to 9.98), sandy to silty loam in texture at surface and loamy sand to sandy loam in texture at the subsurface. Five soil series were characterized and mapped in the course of the investigation. Four soil series belonged to the aeolian plains covering 74% area of NCP and these are Sanchore, Dhorimana, Chohtan and Dune complex whereas one soil series i.e. Chitalwana was identified belonging to alluvial plains covering 10% area of NCP. Organic carbon content ranged from 0.03 to 0.42% in the surface soils with a decreasing trend along the depth. Available N, P and K content in surface soils ranged from 61.9 to 191.0 kg ha-1, 1.41 to 47.84 kg ha-1 and 56.25 to 652.50 kg ha-1, respectively. Similarly, Fe, Mn, Zn and Cu ranged from 0.85 to 13.46 mg kg-1, 1.72 to 14.55 mg kg-1, 0.08 to 2.40 mg kg-1 and 0.02 to 1.38 mg kg-1, respectively. Based on visual interpretation of satellite images and subsequent ground truthing, ten types of landforms have been characterized in the area, which have been categorised under fluvial, aeolian and coastal kinds. Among the landforms of fluvial origin, alluvial plains occur in about 37% of total area under NCP and have been further mapped as younger and older alluvial plain types. Analysis of groundwater in the NCP area of Rajasthan revealed medium sodicity of groundwater with the value of sodium adsorption ratio ranging from 0.15 to 36.31. The residual sodium carbonate of groundwater ranged from almost nil to 5.7 me L-1 with a mean value of 1.1 me L-1. Among the cations and anions, Na+ and Cl- are the dominant ions and their concentrations ranged from 0.27 to 95.50 me L-1 and 1.40 to 92.40 me L-1, respectively. Benchmark characterization of these soil and water resources will help in future assessment and best management of natural resources specifically in canal command area located in arid landscape.